Sabbath finding rest, renewal, and delight in our busy lives - Muller, Wayne (New York Bantam, 1999)
In today's world, with its relentless emphasis on success and productivity, we have lost the necessary rhythm of life, the balance between work and rest. Constantly striving, we feel exhausted and deprived in the midst of great abundance. We long for time with friends and family, we long for a moment to ourselves.
Keywords: Rest --Religious aspects -Christianity.